Polyolefin composition and laminate manufacturing method
By using zinc inorganic salts as neutralizing agents in polyolefin compositions, the adhesive strength and recyclability issues caused by unsaturated carboxylic anhydride ring opening are addressed, resulting in improved moldability and mechanical properties.
Patent Information
- Application Number
- JP2023112387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
AI Technical Summary
The unsaturated carboxylic acid graft group in modified polyolefins, when containing neutralizing agents like fatty acid metal salts, leads to insufficient adhesive strength and recyclability issues due to ring opening of the acid anhydride group, affecting moldability and mechanical strength in laminates.
Incorporating a zinc inorganic salt compound, such as zinc oxide, as a neutralizing agent in a polyolefin composition to suppress the ring opening of unsaturated carboxylic anhydride, maintaining adhesiveness with barrier resins and improving recyclability.
The polyolefin composition exhibits excellent adhesive strength and recyclability by preventing ring opening of unsaturated carboxylic anhydride, ensuring good moldability and mechanical properties, even after long-term storage.
Smart Images

Figure 2025009399000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyolefin composition. The present invention also relates to a method for producing a laminate having an adhesive layer made of the polyolefin composition. [Background technology]
[0002] Modified polyolefins obtained by graft polymerization of unsaturated carboxylic acids or their derivatives onto olefin polymers mainly composed of ethylene or propylene are well known and are widely used industrially. In particular, modified polyolefins graft-polymerized with maleic anhydride have good adhesion to barrier resins such as polyamides, ethylene-vinyl alcohol copolymers, and thermoplastic polyesters, and are therefore widely used as adhesive layer materials for bonding layers together in laminates using barrier resins (Patent Document 1). In addition, modified polyolefins graft-polymerized with maleic anhydride are also used as compatibilizers to finely disperse barrier resins such as polyamides and ethylene-vinyl alcohol copolymers in recycled resin layers with polyethylene or polypropylene as the matrix, which are used in combination with barrier resins in laminates.
[0003] It has been known in the past to compound these modified polyolefins with other polyolefins in order to satisfy market demands. For example, in Patent Document 1, a modified polyethylene grafted with an unsaturated carboxylic acid is blended with a polyethylene copolymerized with ethylene as the main component, propylene, and 1-butene. Patent Document 2 proposes an adhesive polypropylene resin composition in which a modified polypropylene grafted with an unsaturated carboxylic acid is blended with a polypropylene having propylene as the main component and copolymerized with ethylene, and a polyethylene having ethylene as the main component and copolymerized with 1-hexene.
[0004] Patent Document 3 proposes blending a fatty acid zinc salt with a polyolefin resin containing at least one of a carboxyl group and an acid anhydride group that constitutes the adhesive resin layer, with the objective of providing a multilayer structure having an adhesive resin layer between a thermoplastic resin layer and a gas barrier resin layer, in which interfacial roughness that occurs at the lamination interface between the gas barrier layer and the adhesive resin layer is highly suppressed and the multilayer structure has a high level of excellent transparency. In Patent Document 3, instead of calcium stearate which is blended as a neutralizer for a polymerization metal catalyst in the conventional technology of Patent Document 3 to improve adhesion, a zinc salt of a fatty acid such as zinc stearate is used to prevent interface roughness and improve transparency. As described in Patent Document 3, a modified polyolefin composition containing fatty acid metal salts is used in the laminate, so when recycled polyolefin from such a laminate is used, the recycled polyolefin will contain these fatty acid metal salts. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 021149 [Patent Document 2] JP 2019-156971 A [Patent Document 3] International Publication No. 2019-208169 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the unsaturated carboxylic acid graft groups contained in the modified polyolefin are affected by the neutralizing agents contained in the polyolefin, such as zinc stearate and calcium stearate, which are contained in the polyolefin to achieve other required physical properties such as moldability, and therefore the adhesive strength between the barrier resin layer, such as an ethylene-vinyl alcohol copolymer, of the laminate using this and the modified polyolefin composition layer acting as an adhesive layer is insufficient. In addition, the polyolefin to be blended with the modified polyolefin may be recycled scraps generated during molding or waste bottles after use. However, even in this case, the recycle moldability and the mechanical strength of the recycled layer may not be sufficient due to the influence of fatty acid metal salts contained in the waste materials.
[0007] As a result of investigations, the present inventors have found that such problems in adhesive strength and recyclability in modified polyolefin compositions are caused by ring-opening over time of the acid anhydride groups in the unsaturated carboxylic acid graft groups of the modified polyolefin.
[0008] In Patent Document 3, a fatty acid zinc salt is blended with the modified polyolefin. However, as shown in Comparative Examples 1 to 3 below, the organic acid portion of the fatty acid zinc salt reacts with the unsaturated carboxylic acid anhydride to open the acid anhydride group, resulting in a decrease in adhesive strength and recyclability.
[0009] The present invention has been made in view of the above circumstances, and has an object to provide a polyolefin composition which can suppress ring-opening of carboxylic anhydrides present in the polyolefin composition, thereby preventing deterioration of adhesion to barrier resins and the like, and further suppresses ring-opening of unsaturated carboxylic anhydrides even during long-term storage. [Means for solving the problem]
[0010] As a result of intensive research into achieving the above object, the present inventors have found that the above problems can be solved by using a polyolefin composition containing an inorganic chloride of zinc as a neutralizing agent, and have thus completed the present invention. That is, the gist of the present invention is as follows.
[0011] [1] A polyolefin composition comprising the following components (A) to (C): Component (A): Modified polyolefin modified with unsaturated carboxylic acid anhydride Component (B): Unmodified polyolefin Component (C): Inorganic salt compound of zinc
[0012] [2] The polyolefin composition according to [1], wherein the inorganic salt compound of zinc is zinc oxide.
[0013] [3] The polyolefin composition according to [1] or [2], wherein the content of component (C) is 0.01 parts by mass or more and 0.30 parts by mass or less per 100 parts by mass of the total of components (A) and (B).
[0014] [4] A method for producing a laminate having an adhesive layer made of a polyolefin composition containing the following components (A) to (C), characterized in that a polyolefin composition having a ring-opening rate of unsaturated carboxylic acid anhydride in the polyolefin composition of less than 30% is used. Component (A): Modified polyolefin modified with unsaturated carboxylic acid anhydride Component (B): Unmodified polyolefin Component (C): Inorganic salt compound of zinc
[0015] [5] A laminate having an adhesive layer made of the polyolefin composition according to [1] or [2].
[0016] [6] A bottle made of the laminate described in [5].
[0017] [7] A tube made of the laminate described in [5].
[0018] [8] A pipe made of the laminate described in [5]. Effect of the Invention
[0019] According to the present invention, a polyolefin composition having excellent adhesive strength is provided by suppressing ring-opening of unsaturated carboxylic anhydride present in the polyolefin composition. Furthermore, the recycled layer obtained by using the polyolefin composition of the present invention can prevent ring-opening of unsaturated carboxylic anhydride present in the polyolefin composition, so that ethylene-vinyl alcohol copolymer and the like contained in the recycled layer can be finely dispersed, and the recycled layer has excellent moldability and mechanical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The following describes in detail an embodiment of the present invention. However, the following description is an example of an embodiment of the present invention, and the present invention is not limited to the contents of the following description as long as it does not go beyond the gist of the present invention.
[0021] [Polyolefin Composition] The polyolefin composition of the present invention comprises the following components (A) to (C): Component (A): Modified polyolefin modified with unsaturated carboxylic acid anhydride Component (B): Unmodified polyolefin Component (C): Inorganic salt compound of zinc
[0022] [Component (A): Modified polyolefin modified with unsaturated carboxylic acid anhydride] The modified polyolefin modified with an unsaturated carboxylic anhydride of component (A) (hereinafter, sometimes simply referred to as "modified polyolefin") is a resin obtained by graft-modifying a polyolefin with an unsaturated carboxylic anhydride. Here, "graft-modified" means that an unsaturated carboxylic anhydride is bonded to a polyolefin. The bonding position of the unsaturated carboxylic anhydride in the modified polyolefin is not particularly limited, and it is sufficient that the unsaturated carboxylic anhydride is introduced into at least one of the main chain terminal and the side chain of the polyolefin resin.
[0023] The polyolefin used as the raw material to be modified with the unsaturated carboxylic anhydride (hereinafter, sometimes referred to as "raw material polyolefin") is not particularly limited, but includes ethylene homopolymers, propylene homopolymers, copolymers of ethylene and other monomers, copolymers of propylene and other monomers, etc. Examples of other monomers include α-olefins having 3 to 20 carbon atoms such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene, as well as vinyl acetate, vinyl alcohol, (meth)acrylic acid, and (meth)acrylic acid esters. Here, (meth)acrylic acid means acrylic acid and / or methacrylic acid (hereinafter, the same applies).
[0024] Specific examples of raw material polyolefins include ethylene homopolymers such as high-pressure low-density polyethylene (LDPE) and high-density polyethylene (HDPE), ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-hexene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-octene copolymers, ethylene-butene-hexene copolymers, ethylene-butene-octene copolymers, ethylene-hexene-octene copolymers, and ethylene-α-olefin copolymers such as ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, and ethylene-(meth)acrylic acid copolymers. Ethylene-based (co)polymers such as ethylene-ethyl (meth)acrylate copolymer, ethylene-ethyl (meth)acrylate copolymer, and ethylene-(meth)acrylic acid-methyl (meth)acrylate copolymer; propylene homopolymer, propylene-ethylene random copolymer, propylene-butene random copolymer, propylene-ethylene-hexene random copolymer, propylene-ethylene-octene random copolymer, propylene-butene-hexene random copolymer, propylene-butene-octene random copolymer, propylene-hexene-octene random copolymer, and propylene-ethylene block copolymer; butene (co)polymers. Here, "(co)polymer" is a general term for polymers and copolymers.
[0025] Here, the ethylene-based copolymer, propylene-based copolymer, and butene-based copolymer respectively mean copolymers containing ethylene, propylene, or butene in a proportion of 50 mol % or more of all monomer units constituting the copolymer.
[0026] These raw material polyolefins may be used alone or in any combination and ratio of two or more kinds.
[0027] Among these, ethylene homopolymer, ethylene-α-olefin copolymer, and ethylene-vinyl acetate copolymer, which are ethylene-based (co)polymers, and propylene homopolymer and propylene-ethylene random copolymer, which are propylene-based (co)polymers, are preferred because they are inexpensive, easy to obtain, and are economically superior. From the viewpoint of mechanical properties, ethylene homopolymer, ethylene-α-olefin copolymer, propylene homopolymer, and propylene-ethylene random copolymer are more preferred as raw material polyolefins.
[0028] The density of the raw material polyolefin (JIS K7112) is not particularly limited, but is preferably 0.85 g / cm 3 More preferably, it is 0.87 g / cm 3 On the other hand, 0.98 g / cm 3 Preferably less than 0.97 g / cm 3 The melt flow rate (MFR) of the raw material polyolefin is not particularly limited, but is preferably 0.01 to 50 g / 10 min, more preferably 0.1 to 30 g / 10 min, from the viewpoint of moldability. Here, the MFR of the polyolefin means a value at 190° C. and a load of 2.16 kg when the polyolefin is an ethylene-based (co)polymer or a butene-based (co)polymer, and means a value at 230° C. and a load of 2.16 kg when the polyolefin is a propylene-based (co)polymer.
[0029] The unsaturated carboxylic acid anhydride used for graft modification of the raw material polyolefin is not particularly limited, but representative examples include the anhydrides of acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid.
[0030] Specific examples of the unsaturated carboxylic acid anhydride include maleic anhydride, himic anhydride, itaconic anhydride, and citraconic anhydride.
[0031] The unsaturated carboxylic acid anhydrides can be used alone or in any combination and ratio of two or more kinds.
[0032] Among these, maleic anhydride is particularly preferred because of its low electron density and high reactivity.
[0033] Graft modification of raw polyolefin can be carried out by various conventionally known methods. Modification methods include, but are not limited to, a melt modification method in which an unsaturated carboxylic anhydride is added to a molten raw polyolefin to perform graft copolymerization, and a solution modification method in which an unsaturated carboxylic anhydride is added to a raw polyolefin dissolved in a solvent to perform graft copolymerization. Among these, from the viewpoint of hygiene, the melt modification method that does not require the use of a solvent is preferred, and graft modification using an extruder is more preferred. In addition, in order to perform graft modification efficiently, it is preferred to perform modification in the presence of a radical initiator.
[0034] The radical initiator is not particularly limited, but is preferably an organic peroxide or an azo compound, and more preferably an organic peroxide. Specifically, dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,4-bis(t-butylperoxyisopropyl)benzene, 1,1-bis(t-butylperoxy)cyclohexane, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,2-bis(4,4-t-butylperoxycyclohexyl)propane, 2,2-bis(t-butylperoxy)butane, and 1,1-bis(t-butylperoxy)cyclododecane; t-butylperoxyacetate, t-butylperoxy-2-ethylhexanoate, t-butylperoxypivalate, t-butylperoxylaurate, t-butylperoxybenzoate, t-butylperoxyisopropyl peroxy esters such as diethyl carbonate, t-butyl peroxymaleic acid, di-t-butyl peroxy isophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3, and 2,5-dimethyl-2,5-di(toluylperoxy)hexane; diacyl peroxides such as di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, and dibenzoyl peroxide; hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, and 2,5-dimethyl-2,5-di(hydroperoxy)hexane; and ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide, but are not particularly limited thereto.
[0035] The radical initiator may be used alone or in any combination and ratio of two or more kinds.
[0036] Among these, radical initiators having a decomposition temperature of 100° C. or higher, at which the half-life is 1 minute, are preferred from the viewpoint of graft modification efficiency. Specifically, dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, and peroxy esters such as t-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3 are preferred.
[0037] The amount of the radical initiator used is not particularly limited, but is preferably 0.001 to 1 part by mass per 100 parts by mass of the raw material polyolefin.
[0038] The content of unsaturated carboxylic acid anhydride in the modified polyolefin (hereinafter sometimes referred to as "graft rate") varies depending on the type of raw material polyolefin and the unsaturated carboxylic acid anhydride used for modification, and is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, relative to the total amount of modified polyolefin, and is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less. When the graft rate is equal to or higher than the lower limit of the above-mentioned preferred value, the adhesion to a resin having polarity tends to be good. On the other hand, when the graft rate is equal to or lower than the upper limit of the above-mentioned preferred value, it is possible to prevent partial crosslinking of the raw material polyolefin itself during grafting, which would result in a decrease in moldability, or deterioration of the product appearance due to the generation of fish eyes or foreign matter.
[0039] Here, the graft ratio can be measured by press-molding the modified polyolefin directly into a sheet having a thickness of 100 μm to prepare a test sample, and using infrared absorption spectroscopy, the graft ratio can be determined from the absorption characteristic of the unsaturated carboxylic anhydride in the resin. -1 It can be determined by measuring the carbonyl characteristic absorption (C=O stretching vibration band). In the graft modification of the raw material polyolefin, unsaturated carboxylic acid anhydride that has not reacted with the raw material polyolefin may remain, but the graft ratio in this specification means the value obtained when the modified polyolefin is measured by the above-mentioned method, as described above.
[0040] The density of the modified polyolefin (JIS K7112) is not particularly limited, but is preferably 0.85 g / cm 3 More preferably, it is 0.87 g / cm 3 On the other hand, 0.98 g / cm 3 Preferably less than 0.97 g / cm 3 The following is the result.
[0041] The melt flow rate (MFR) of the modified polyolefin is not particularly limited, but is preferably 0.01 to 100 g / 10 min, and more preferably 0.1 to 30 g / 10 min. Here, the MFR of the modified polyolefin means a value at 190° C. and a load of 2.16 kg when the raw polyolefin is an ethylene (co)polymer or a butene (co)polymer, and means a value at 230° C. and a load of 2.16 kg when the raw polyolefin is a propylene (co)polymer.
[0042] As modified polyolefins suitable for the present invention, commercially available products can be used. For example, one having the above-mentioned properties can be appropriately selected from the "Modic (registered trademark)" series manufactured by Mitsubishi Chemical Corporation.
[0043] These components (A) may be used alone or in combination of two or more types having different monomer compositions, physical properties, etc.
[0044] [Component (B): Unmodified polyolefin] As the unmodified polyolefin of component (B), the above-mentioned raw material polyolefins can be used. Among these, ethylene homopolymer, ethylene-α-olefin copolymer, and ethylene-vinyl acetate copolymer, which are ethylene-based (co)polymers, and propylene homopolymer and propylene-ethylene random copolymer, which are propylene-based (co)polymers, are preferred because they are inexpensive, easy to obtain, and economically superior. From the viewpoint of mechanical properties, ethylene homopolymer, ethylene-α-olefin copolymer, propylene homopolymer, and propylene-ethylene random copolymer are more preferred as unmodified polyolefins. As the unmodified polyolefin suitable for the present invention, a commercially available product can be used. For example, one having the above-mentioned properties can be appropriately selected from the "Kamal (registered trademark)" series manufactured by SPDC and used.
[0045] These components (B) may be used alone or in combination of two or more types having different monomer compositions, physical properties, etc.
[0046] [Component (C): Inorganic salt compound of zinc] The polyolefin composition of the present invention contains an inorganic salt compound of zinc as component (C). The inorganic salt compound of zinc does not contain an organic acid salt group containing carbon atoms and hydrogen atoms. As the inorganic salt compound of zinc, zinc oxide is preferred from the viewpoint of low reactivity with the unsaturated carboxylic anhydride in the modified polyolefin.
[0047] [Other ingredients] The polyolefin composition of the present invention may contain resin components other than component (A) and component (B) (hereinafter sometimes referred to as "other resins"), various additives, fillers, etc., within the scope of not significantly impairing the effects of the present invention. The other components may be used alone or in any combination and ratio of two or more.
[0048] Other resins include thermoplastic resins such as polyphenylene ether resins; polyamide resins such as nylon 6, nylon 66, and nylon 11; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; (meth)acrylic resins such as polymethyl methacrylate resins; and styrene resins such as polystyrene; as well as various thermoplastic elastomers.
[0049] Examples of the additives include various heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, antiaging agents, nucleating agents, plasticizers, impact modifiers, compatibilizers, defoamers, thickeners, crosslinking agents, surfactants, lubricants, release agents, antiblocking agents, processing aids, antistatic agents, flame retardants, flame retardant assistants, colorants, and fillers.
[0050] The polyolefin composition of the present invention may also contain a tackifier as another component. Here, the tackifier may be an amorphous resin that is solid at room temperature, such as a petroleum resin, a rosin resin, a terpene resin, or a hydrogenated product thereof. However, if a large amount of tackifier is contained in the polyolefin composition, smoke may be generated during molding, or the tackifier may leak into the food or drink when used as a material for packaging oily food or drink. For this reason, when a tackifier is used, the content of the tackifier in the polyolefin composition is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 2% by mass or less, particularly preferably less than 1% by mass, and most preferably does not substantially contain a tackifier. Even when a tackifier is not used, the polyolefin composition of the present invention has excellent high-speed extrusion laminate moldability, and when used as an adhesive layer in a laminate, it has good adhesion to adjacent resin layers, and can maintain good adhesion to adjacent resin layers even under high temperature and high humidity environments.
[0051] Examples of the petroleum resin include aliphatic petroleum resin, aromatic petroleum resin, copolymers thereof, and hydrogenated products thereof. Examples of the petroleum resin skeleton include C5 resin, C9 resin, C5 / C9 copolymer resin, cyclopentadiene resin, polymer of vinyl-substituted aromatic compound, copolymer of olefin / vinyl-substituted aromatic compound, copolymer of cyclopentadiene compound / vinyl-substituted aromatic compound, or hydrogenated products thereof. The rosin resin is a natural resin containing abietic acid as a main component, and examples thereof include natural rosin, polymerized rosin derived from natural rosin, stabilized rosin obtained by disproportionating or hydrogenating natural rosin or polymerized rosin, unsaturated acid-modified rosin obtained by adding unsaturated carboxylic acids to natural rosin or polymerized rosin, natural rosin ester, modified rosin ester, and polymerized rosin ester. The terpene resin may be an aromatic terpene resin such as a polyterpene resin or a terpene phenol resin. Examples of suitable terpene resins include terpene resins, aromatic modified terpene resins, and hydrogenated products thereof.
[0052] Examples of the heat stabilizer and antioxidant include hindered phenols, phosphorus compounds, hindered amines, sulfur compounds, copper compounds, and alkali metal halides.
[0053] The polyolefin composition of the present invention is preferably blended with an antiblocking agent as an additive. Blending of the antiblocking agent tends to improve the blocking resistance between pellets during the pellet production process of the polyolefin composition of the present invention, and during subsequent storage, transportation, etc. Examples of the antiblocking agent include polyolefin fine powder, polyethylene wax, and dispersions thereof.
[0054] Flame retardants are broadly classified into halogen-based and non-halogen-based flame retardants, with non-halogen-based flame retardants being preferred from an environmental perspective. Examples of non-halogen-based flame retardants include phosphorus-based flame retardants, hydrated metal compound (aluminum hydroxide, magnesium hydroxide) flame retardants, nitrogen-containing compound (melamine-based, guanidine-based) flame retardants, and inorganic compound (borate, molybdenum compound) flame retardants.
[0055] Fillers are broadly classified into organic fillers and inorganic fillers. Examples of organic fillers include starch, cellulose fine particles, wood flour, soybean pulp, rice husks, bran, and other naturally derived polymers and modified products thereof. Examples of inorganic fillers include talc, calcium carbonate, zinc carbonate, wollastonite, silica, alumina, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, sodium aluminosilicate, magnesium silicate, glass balloons, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, metal fibers, metal whiskers, ceramic whiskers, potassium titanate, boron nitride, graphite, and carbon fibers.
[0056] [Mixing ratio] In the polyolefin composition of the present invention, the content of component (A) is preferably 1 to 90% by mass relative to 100% by mass of the total of components (A), (B) and (C). From the viewpoints of adhesion to a polyethylene resin in a resin layer described later and the biomass content of the polyolefin composition itself, the lower limit of the content of component (A) is preferably 2% by mass or more, more preferably 5% by mass or more. On the other hand, from the viewpoint of moldability, the upper limit of the content of component (A) is preferably 80% by mass or less, more preferably 40% by mass or less.
[0057] In the polyolefin composition of the present invention, the content of component (B) is preferably 50 to 99% by mass relative to 100% by mass of the total of components (A), (B) and (C). From the viewpoint of adhesion to the polyethylene resin of the resin layer described below, the lower limit of the content of component (B) is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more. On the other hand, from the viewpoint of heat-resistant adhesion, the upper limit is preferably 98% by mass or less, more preferably 97% by mass or less, and even more preferably 96% by mass or less.
[0058] The polyolefin composition of the present invention preferably contains 0.01 to 0.30 parts by mass of component (C) relative to 100 parts by mass of the total of components (A) and (B). By making the content of component (C) 0.01 parts by mass or more, it is easy to obtain the effect as a neutralizing agent, and by making it 0.30 parts by mass or less, it is easy to maintain a good appearance of the obtained molded article. From the above viewpoints, the content of component (C) is preferably 0.02 parts by mass or more, more preferably 0.03 parts by mass or more, and preferably 0.28 parts by mass or less, more preferably 0.25 parts by mass or less, relative to 100 parts by mass of the total of components (A) and (B).
[0059] When the polyolefin composition of the present invention contains the above-mentioned other resins, the content is not limited, but is usually 0.1 to 20 mass%, preferably 0.5 to 10 mass%, based on 100 mass% of the polyolefin composition. If the content of the other resins is equal to or less than the upper limit, the resulting polyolefin composition can have sufficient adhesion to resins having polar groups.
[0060] The content of the additives in the polyolefin composition of the present invention is not limited, but is usually 0.01 to 10 mass%, preferably 0.2 to 5 mass%, based on 100 mass% of the polyolefin composition. If the content of the additives is equal to or less than the upper limit, the resulting polyolefin composition can have sufficient adhesion to a resin having a polar group. When the polyolefin composition of the present invention is used as a master batch, these additives can be contained at a concentration of 2 to 50 times, preferably 3 to 30 times, the above-mentioned content.
[0061] [Method of producing polyolefin composition] The polyolefin composition of the present invention can be obtained by mixing the above-mentioned components in a predetermined ratio. There is no particular restriction on the mixing method as long as the raw material components are uniformly dispersed. That is, by mixing the above-mentioned raw material components simultaneously or in any order, a polyolefin composition in which each component is uniformly dispersed can be obtained. For more uniform mixing and dispersion, it is preferable to melt-mix a predetermined amount of the above-mentioned raw material components. For example, the raw material components of the polyolefin composition of the present invention may be mixed in any order and then heated, or all the raw material components may be mixed while melting sequentially, or the raw material components may be appropriately blended (dry blended) and melt-mixed during molding to produce the desired molded product.
[0062] The mixing method and mixing conditions are not particularly limited as long as each raw material component is mixed uniformly, but from the viewpoint of productivity, for example, a method of mixing the raw materials using a tumbler blender, V blender, ribbon blender, Henschel mixer, etc., and melt-kneading using a continuous kneader such as a single-screw extruder or a twin-screw extruder, and a batch-type kneader such as a mill roll, a Banbury mixer, or a pressure kneader is preferable. The manufacturing conditions when producing a polyolefin composition by these methods are not limited, and can be appropriately set under well-known conditions. The temperature during melt mixing may be a temperature at which at least one of the raw material components is in a molten state, but a temperature at which all the raw material components used are melted is usually selected, and it can be generally performed in the range of 150 to 250 ° C.
[0063] [Laminate] The laminate of the present invention has an adhesive layer made of the polyolefin composition of the present invention, and is usually a laminate having a laminate structure of two or more layers including a resin layer arranged so as to be in contact with the adhesive layer. Examples of the form of the laminate of the present invention include a laminate sheet, a laminate film, a laminate tube, etc. Here, both "sheet" and "film" mean planar molded bodies and are synonymous. In addition, the resin layer is preferably a gas barrier resin layer made of a resin having a polar group such as an ethylene-vinyl alcohol copolymer, or a polyethylene-based resin layer described below.
[0064] [Adhesive layer] The thickness of the adhesive layer made of the polyolefin composition of the present invention in the laminate of the present invention is not limited, and can be arbitrarily set depending on the layer structure, use, shape of the final product, required physical properties, etc., but is usually 1% or more, preferably 5% or more, and usually 20% or less, preferably 10% or less, relative to the total thickness. For example, the thickness of the adhesive layer is preferably in the range of 1 to 100 μm, more preferably in the range of 2 to 50 μm, and even more preferably in the range of 3 to 20 μm. If the thickness of the adhesive layer made of the polyolefin composition of the present invention is the above lower limit or more, the adhesiveness is good, and if it is the above upper limit or less, the strength of the laminate is good. Here, the thickness of the adhesive layer is the thickness per one adhesive layer.
[0065] [Resin layer having polar groups] The resin having a polar group is a resin having a monovalent or divalent polar group in the molecule. Examples of the monovalent or divalent polar group include monovalent functional groups such as hydroxyl groups, carboxyl groups, amino groups, alkyl ester groups, isocyanate groups, and glycidyl groups, and divalent functional groups that form ester bonds, amide bonds, urethane bonds, urea bonds, ether bonds, and carbonyl bonds.
[0066] As such a resin having a polar group, for example, an olefin polymer, a polyamide resin, or an ethylene-vinyl alcohol copolymer having a polar group is preferably used, and these resins can also be imparted with gas barrier properties. Among these, an ethylene-vinyl alcohol copolymer (EVOH) is preferred.
[0067] Specific examples of olefin polymers having polar groups include modified ethylene-propylene copolymers and silane-modified polyolefins.
[0068] Specifically, the polyamide resin preferably used is nylon 6, nylon 66, nylon 610, nylon 9, nylon 11, nylon 12, nylon 6 / 66, nylon 66 / 610, nylon 6 / 11, MXD nylon, amorphous nylon, or terephthalic acid / adipic acid / hexamethylenediamine copolymer. Among them, nylon 6, nylon 66, and nylon 6 / 66, which have excellent melting points and rigidity, are preferred.
[0069] The ethylene-vinyl alcohol copolymer is preferably a copolymer having an ethylene content of 15 to 65 mol%, more preferably 25 to 48 mol%. Such an ethylene-vinyl alcohol copolymer can be produced by saponifying a copolymer of ethylene and vinyl acetate, and the copolymer is used so that the saponification degree is preferably 50% or more, more preferably 90% or more. The upper limit of the saponification degree is 100%. If the ethylene content of the ethylene-vinyl alcohol copolymer is too low, it is prone to thermal decomposition, difficult to melt mold, has poor stretchability, and is prone to water absorption and swelling, resulting in poor water resistance. On the other hand, if the ethylene content of the ethylene-vinyl alcohol copolymer is too high, gas permeability resistance tends to decrease. Also, if the degree of saponification is too low, gas permeability resistance tends to decrease.
[0070] The thickness of the gas barrier resin layer having a polar group, such as an ethylene-vinyl alcohol copolymer, is not particularly limited and is appropriately determined depending on the application, type of resin, required properties, etc., but is usually 2 to 200 μm, preferably 3 to 100 μm.
[0071] The laminate made of these resins may be a laminate of two or more kinds.
[0072] [Polyethylene resin layer] Since the polyolefin composition of the present invention has excellent adhesion to polyethylene resins, it is preferred that the composition has a polyethylene resin layer so as to be in contact with an adhesive layer made of the polyolefin composition of the present invention.
[0073] The polyethylene resin of the polyethylene resin layer is preferably an ethylene homopolymer or an ethylene copolymer, such as a biopolyethylene resin or a petroleum-derived polyethylene resin. As a polyethylene-based resin, specifically, high-density polyethylene (HDPE, density 0.940 g / cm 3 or more), medium density polyethylene (MDPE, density 0.925 or more 0.940g / cm 3 less than 0.925g / cm 3 less than 0.910g / cm), linear low density polyethylene (LLDPE, density 0.910-0.925g / cm 3 These may be used alone or in combination of two or more.
[0074] The melt flow rate (MFR) of the polyethylene resin (190°C, load 2.16 kg) is usually 0.1 to 50 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 1.5 to 35 g / 10 min. If the MFR is equal to or lower than the upper limit, the film formability and stability are excellent, and if it is equal to or higher than the lower limit, the melt extrudability is excellent.
[0075] From the viewpoint of moldability, the thickness of the polyethylene resin layer is preferably 1 to 10,000 μm, more preferably 5 to 5,000 μm, and further preferably 10 to 1,000 μm, where the thickness of the polyethylene resin layer is the thickness per one polyethylene resin layer.
[0076] The above-mentioned resin layer having a polar group and the polyethylene resin layer may contain one or more of the components (A) to (C) in the polyolefin composition of the present invention, and may also contain the above-mentioned other components and additives that may be contained in the polyolefin composition of the present invention, within the scope that does not impair the object thereof.
[0077] [Other layers] The laminate of the present invention has a laminate structure including at least an adhesive layer made of the polyolefin composition of the present invention and a resin layer in contact with the adhesive layer, and may further include layers other than those described above. The other layers are not particularly limited, and examples thereof include resin layers made of polycarbonate resins, styrene-based resins such as polystyrene (GPPS), high impact polystyrene (HIPS), and styrene-acrylonitrile graft copolymers (ABS resins), and other thermoplastic resin layers such as olefin polymers other than ethylene-based resins, polyphenylene ether-based resins, polyoxymethylene-based resins such as polyoxymethylene homopolymers and polyoxymethylene copolymers, and acrylic / methacrylic resins such as polymethyl methacrylate-based resins.
[0078] [Layer composition] The laminate of the present invention may be, for example, a five-layer laminate formed by laminating polyethylene resin layers on both sides of a resin layer having a polar group via an adhesive layer made of the polyolefin composition of the present invention, i.e., a laminate having a layer structure of polyethylene resin layer / adhesive layer made of the polyolefin composition of the present invention / resin layer having a polar group / adhesive layer made of the polyolefin composition of the present invention / polyethylene resin layer. In this case, the two polyethylene resin layers may be made of the same polyethylene resin or different polyethylene resins.
[0079] [Laminate thickness] Although the thickness of the laminate of the present invention cannot be generally determined depending on the layer structure, the type of adhesive resin, the application, packaging form, required physical properties, etc., when the laminate of the present invention is a multilayer sheet, the total thickness is preferably 200 to 5,000 μm. When the laminate of the present invention is a multilayer film, the total thickness is preferably 2 to 500 μm, more preferably 3 to 300 μm, and even more preferably 30 to 200 μm.
[0080] [Method for producing laminate] In the method for producing the laminate of the present invention, from the viewpoints of adhesion and recyclability, it is preferable to use a polyolefin composition containing components (A) to (C) in which the ring-opening rate of the unsaturated carboxylic acid anhydride is less than 30% for forming the adhesive layer. Here, the ring-opening rate of the unsaturated carboxylic acid anhydride in the polyolefin composition is the ratio (percentage) of the ring-opened unsaturated carboxylic acid to the total of the ring-opened unsaturated carboxylic acid and the unsaturated carboxylic acid anhydride in the polyolefin composition, and is measured by the method described in the Examples section below.
[0081] In the method for producing a laminate of the present invention, a polyolefin composition having an unsaturated carboxylic anhydride ring-opening rate of less than 30% is used to form an adhesive layer, thereby making it possible to obtain high interlayer adhesive strength. Such a low ring-opening rate is achieved by the polyolefin composition of the present invention, which uses, as a neutralizing agent, an inorganic salt compound of zinc, which has a lower reactivity with unsaturated carboxylic acid anhydrides than conventional fatty acid metal salts. The polyolefin composition of the present invention can also suppress an increase in the ring-opening rate over time after the production of a laminate, and can suppress a decrease in interlayer adhesive strength. . In the method for producing a laminate of the present invention, the ring-opening rate of the unsaturated carboxylic anhydride in the polyolefin composition used for producing the laminate is preferably as low as possible, and is preferably 28% or less, particularly preferably 25% or less. There is no particular lower limit to this ring-opening rate, but it is usually about 1%.
[0082] As a method for producing the laminate of the present invention, various conventionally known methods can be adopted. For example, there is inflation molding by a co-extrusion method in which individual molten resins melted in an extruder are supplied to a multi-layer die and laminated in the die, film or sheet molding by T-die molding, container molding by blow molding, and co-injection molding in which individual molten resins are injected into the same mold with a time lag. In addition, extrusion lamination by co-extrusion of the adherend alone or with other resins, or a method in which the adherend is subjected to corona discharge treatment or flame treatment before lamination during extrusion lamination, and the adhesive surface of the adherend and the polyolefin composition of the present invention are ozone treated immediately before lamination, can also be used. Furthermore, a lamination method by heat lamination, heat sealing, etc. of the polyolefin composition film of the present invention obtained by co-extrusion alone or with other resins and the adherend film can also be used.
[0083] The conditions for these co-extrusion film, sheet, and blow moldings are not particularly limited, but are preferably formed at a die temperature in the range of 180 to 250° C. The conditions for extrusion lamination molding are not particularly limited, but are preferably formed at a die temperature in the range of 280 to 320° C., and the lamination method using heat lamination or heat sealing is not particularly limited, but is preferably formed at a lamination temperature in the range of 160 to 220° C.
[0084] [Molded body] The laminate of the present invention can be molded into a molded article. The molded article obtained by molding the laminate of the present invention can be suitably used as a packaging material such as a lid material or a packaging bag. It is also possible to obtain a multilayer container in the form of a cup or a tray using the laminate of the present invention. In this case, a squeeze molding method is usually adopted, and specific examples thereof include a vacuum molding method, a pressure molding method, a vacuum pressure molding method, and a plug-assisted vacuum pressure molding method. Furthermore, when a multilayer container (laminate structure) in the form of a tube, a pipe, or a bottle is obtained from a multilayer parison (a hollow tubular preform before blowing), a blow molding method is adopted.
[0085] Specific examples of the molding method for molding the laminate of the present invention into a molded article include extrusion blow molding (double-head type, mold moving type, parison shift type, rotary type, accumulator type, horizontal parison type, etc.), cold parison type blow molding, injection blow molding, and biaxial stretch blow molding (extrusion type cold parison biaxial stretch blow molding, injection type cold parison biaxial stretch blow molding, injection molding in-line type biaxial stretch blow molding, etc.). In this case, if necessary, heat treatment, cooling treatment, rolling treatment, printing treatment, dry lamination treatment, solution or melt coating treatment, bag making, deep drawing, box processing, tube processing, split processing, etc. can be performed.
[0086] [Application] The polyolefin composition of the present invention exhibits excellent adhesive strength properties to resins having polar groups, particularly ethylene-vinyl alcohol copolymers, and maintains high interlayer adhesive strength even after various processing steps. Therefore, a molded article made of the laminate of the present invention having the polyolefin composition of the present invention as an adhesive layer exhibits excellent adhesive strength properties, and can also be excellent in strength, heat resistance, gas barrier properties, etc.
[0087] Molded articles made from the laminate of the present invention, for example, containers and lids such as films, sheets, bags, cups, trays, tubes, pipes, and bottles, are useful as various packaging materials for general foods, seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, beverages, cosmetics, pharmaceuticals, and the like, and are particularly suitable as packaging materials for foods.
[0088] The polyolefin composition of the present invention can be suitably used as a constituent material for barrier skin packs, tubes, pipes, bottles, tanks, containers, and the like. EXAMPLES
[0089] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiments of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values of the examples.
[0090] [Raw materials] In the examples and comparative examples of the present invention, the following raw materials were used.
[0091] <Ethylene / α-olefin copolymer> SPDC Linear low-density polyethylene "Kamar (registered trademark)" (MFR: 1.5g / 10min (190℃, 2.16kg load), density: 0.920g / cm 3 )
[0092] <Maleic anhydride modified polyethylene> The maleic anhydride-modified polyethylene used was prepared as follows. MFR2.0g / min, density 0.952g / cm 30.8 parts by mass of maleic anhydride and 0.03 parts by mass of 2,5-dimethyl-di(t-butylperoxy)hexane were added to 100 parts by mass of high-density polyethylene (Novatec (registered trademark), HY350, manufactured by Japan Polyethylene Corporation), mixed in a Henschel mixer, and then melt-kneaded using a 50 mm single-screw extruder manufactured by IKG Corporation under conditions of a screw rotation speed of 50 rpm and a resin temperature of 280 to 290°C, resulting in a MFR of 0.2 g / min and a density of 0.952 g / cm. 3 As a result, maleic anhydride modified polyethylene was obtained. The ring-opening rate of this maleic anhydride modified polyethylene was 5%.
[0093] <Neutralizing agent> Zn-1: Zinc oxide (Wako Pure Chemical Industries, purity 99% or higher) Zn-2: Zinc stearate (Tokyo Chemical Industry Co., Ltd., purity 98% or more)
[0094] [Measurement and evaluation method] The methods for measuring and evaluating various physical properties and characteristics are as follows:
[0095] <Melt flow rate (MFR)> Measurements were performed at 190°C and a load of 10 kg in accordance with JIS K7210 (1999).
[0096] <Ring opening rate> The sample was heat-pressed at 200° C. to prepare a film having a thickness of 100 μm. The infrared absorption spectrum was measured to calculate the ring-opening ratio. The ring-opening rate was determined by the peak of maleic anhydride in the infrared absorption spectrum (1785 cm -1 ) and the peak of maleic acid (1705 cm -1 ) was used to calculate {E2 / (E1+E2)}×100. Samples were prepared by storing the polyolefin compositions obtained in the Examples and Comparative Examples in a place set at a humidity of 50% and a temperature of 23°C, followed by heat pressing, and by storing the samples in the same environment for 6 months, followed by heat pressing. The measured value of the sample after 7 days of storage was recorded as the initial ring-opening ratio, and the measured value of the sample after 6 months of storage was recorded as the ring-opening ratio after 6 months.
[0097] <Adhesive strength> Using the polyolefin compositions obtained in the Examples and Comparative Examples, a 3-type, 5-layer, hollow bottle of 500 mL was produced in a 3-type, 5-layer blow molding machine under the conditions of a set temperature of 200°C, a blow pressure of 0.5 MPa, a mold temperature of 15°C, and a cooling time of 2 minutes. The layer structure of this container was, from the outside, a high-density polyethylene resin layer (Novatec (registered trademark) HB232RN, manufactured by Japan Polyethylene Corporation, density 0.946 g / cm 3 , MFR 0.35g / 10min) / polyolefin composition layer / ethylene-vinyl alcohol copolymer layer (EVAL (registered trademark) F101B, manufactured by Kuraray Co., Ltd.) / polyolefin composition layer / high-density polyethylene resin layer (Novatec (registered trademark) HB232RN, manufactured by Japan Polyethylene Corporation), with layer thicknesses of 1.5mm / 0.1mm / 0.1mm / 0.1mm / 1.5mm. Note that these layer thicknesses are designed to be thicker than the optimum thicknesses of each of the aforementioned preferred layers in order to measure adhesive strength. The side of the resulting container was then cut into a strip of 7 mm width and 120 mm length in the MD direction to prepare a sample for measuring adhesion. This sample was stored for 7 days in a location set at 50% humidity and 23°C temperature, and the adhesion between the second layer (polyolefin composition) and the third layer (ethylene-vinyl alcohol copolymer) was measured from the outside. The strength was measured by making a cut between the second and third layers and peeling at 90°C with an Orientec Tensilon at a tensile speed of 50 mm / min.
[0098] <Reference example 1> 5 parts by mass of maleic anhydride modified polyethylene and 95 parts by mass of ethylene-α-olefin copolymer were mixed and dry blended for 2 minutes, and then melt kneaded at a screw speed of 50 rpm and a resin temperature of 200 to 230°C using a 50 mm single screw extruder manufactured by IKG Co., Ltd. to obtain a polyolefin composition. The MFR, ring opening rate and adhesive strength of this polyolefin composition were evaluated by the methods described above, and the results are shown in Table 1.
[0099] <Example 1> 5 parts by mass of maleic anhydride modified polyethylene, 95 parts by mass of ethylene-α-olefin copolymer, and 0.05 parts by mass of Zn-1 as a neutralizing agent were mixed and dry blended for 2 minutes, and then melt-kneaded using a 50mm single screw extruder manufactured by IKG Corp. at a screw speed of 50 rpm and a resin temperature of 200 to 230°C to obtain a polyolefin composition. The MFR, ring opening rate, and adhesive strength of this polyolefin composition were evaluated by the methods described above, and the results are shown in Table 1.
[0100] <Example 2> Except for using 0.1 parts by mass of Zn-1 as a neutralizing agent, melt kneading was carried out in the same manner as in Example 1 to obtain a polyolefin composition. The MFR, ring opening rate, and adhesive strength of this polyolefin composition were evaluated by the above-mentioned methods, and the results are shown in Table 1.
[0101] <Example 3> Except for using 0.2 parts by mass of Zn-1 as a neutralizing agent, melt kneading was carried out in the same manner as in Example 1 to obtain a polyolefin composition. The MFR, ring opening rate, and adhesive strength of this polyolefin composition were evaluated by the above-mentioned methods, and the results are shown in Table 1.
[0102] <Comparative Examples 1 to 3> Polyolefin compositions were obtained in the same manner as in Example 1, except that the types and compositions of the raw materials used were changed as shown in Table 1. The MFR, ring opening rate, and adhesive strength of these polyolefin compositions were evaluated by the above-mentioned methods, and the results are shown in Table 1.
[0103] [Table 1]
[0104] From the above results, the following can be seen: As shown in Examples 1 to 3, the polyolefin composition using Zn-1, an inorganic zinc salt compound, as a Zn-based neutralizing agent showed a lower ring-opening rate and higher adhesive strength than Comparative Examples 1 to 3 using polyolefin compositions containing Zn-2, a fatty acid zinc salt. The ring-opening rate was also maintained low after 6 months. This is believed to be because Zn-1 used in Examples 1 to 3 is an inorganic salt compound and does not contain an organic acid moiety, so the reaction with maleic anhydride was suppressed. The ring-opening rates of the polyolefin compositions of Comparative Examples 1 to 3 were higher immediately after production compared to those of Examples 1 to 3. In the hollow bottles using the polyolefin compositions of Comparative Examples 1 to 3, the adhesive strength between the polyolefin composition layer and the barrier resin layer made of the polyolefin composition was low, and the bottles were poor in reliability due to the possibility of peeling when dropped. In addition, the polyolefin compositions of Comparative Examples 1 to 3 also had high ring-opening rates after six months of storage. This shows that the polyolefin compositions of Comparative Examples 1 to 3 have poor dispersibility of the barrier resin, and when recycling scraps or after use, there is a lot of adhesion derived from the barrier resin on the die, so that the polyolefin compositions are poor in moldability during recycling and the mechanical properties of the recycled resin layer are also poor.
[0105] From the above, it can be seen that a polyolefin composition containing Zn-1 as a neutralizing agent has a low ring-opening rate of maleic anhydride, has excellent adhesion to barrier resins, and can be used to produce packaging materials such as bottles with excellent barrier properties and reliability.Furthermore, when the scraps of the packaging materials or the packaging materials are recycled and molded, there is less adhesion to the die of the molding machine, and a recycled resin layer with excellent mechanical properties can be formed. [Industrial Applicability]
[0106] The polyolefin composition of the present invention has excellent adhesion to barrier resins. Moreover, the polyolefin composition of the present invention can suppress ring opening of unsaturated carboxylic anhydrides even after long-term storage, so that the polyolefin composition of the present invention has excellent recyclability and excellent mechanical strength of the resulting recycled layer. Therefore, the polyolefin composition of the present invention can be suitably used as a constituent material for barrier skin packs, tubes, bottles, tanks, containers, etc.
Claims
1. A polyolefin composition comprising the following components (A) to (C): Component (A): Modified polyolefin modified with an unsaturated carboxylic acid anhydride Component (B): Unmodified polyolefin Component (C): Inorganic salt compound of zinc
2. 2. The polyolefin composition of claim 1, wherein said inorganic salt compound of zinc is zinc oxide.
3. The polyolefin composition according to claim 1 or 2, wherein the content of the component (C) is 0.01 parts by mass or more and 0.30 parts by mass or less per 100 parts by mass of the total of the components (A) and (B).
4. A method for producing a laminate having an adhesive layer made of a polyolefin composition containing the following components (A) to (C), characterized in that a polyolefin composition is used having a ring-opening rate of less than 30%, calculated as a ratio of a carboxylic acid consisting of a ring-opened unsaturated carboxylic anhydride, a carboxylic acid consisting of a ring-opened unsaturated carboxylic anhydride, and an unsaturated carboxylic anhydride in the polyolefin composition: Component (A): Modified polyolefin modified with an unsaturated carboxylic acid anhydride Component (B): Unmodified polyolefin Component (C): Inorganic salt compound of zinc
5. A laminate having an adhesive layer made of the polyolefin composition according to claim 1 or 2.
6. A bottle comprising the laminate according to claim 5.
7. A tube comprising the laminate according to claim 5.
8. A pipe comprising the laminate according to claim 5.
Citation Information
Patent Citations
Polyolefin composition and laminate
JP2019156971A
Multilayer structure, resin composition for adhesive resin layers, and method for producing multilayer structure
WO2018021149A1
Adhesive resin composition and laminate
WO2019208169A1